2011
DOI: 10.1002/wsb.53
|View full text |Cite
|
Sign up to set email alerts
|

Road bias for deer density estimates at 2 national parks in Maryland

Abstract: Estimating the population density of deer is an essential task for public agencies that plan a herd reduction. Distance sampling has been increasingly utilized to estimate population density, and is used by the National Park Service to estimate white‐tailed deer (Odocoileus virginianus) densities throughout the eastern United States. Many of these surveys are conducted along public roads due to limited resources and accessibility, which may violate a critical assumption of distance sampling and potentially int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
43
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(45 citation statements)
references
References 14 publications
(20 reference statements)
2
43
0
Order By: Relevance
“…Distance sampling estimates may be biased when the detection probability is variable across space and time. Detection probability in our study was estimated to be <1, which is consistent with other spotlighting efforts (Collier et al , McShea et al ). LaRue et al () and Beaver et al () reported that distance sampling overestimated density for deer using spotlight observations in comparison with other survey designs, which is consistent with our results.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Distance sampling estimates may be biased when the detection probability is variable across space and time. Detection probability in our study was estimated to be <1, which is consistent with other spotlighting efforts (Collier et al , McShea et al ). LaRue et al () and Beaver et al () reported that distance sampling overestimated density for deer using spotlight observations in comparison with other survey designs, which is consistent with our results.…”
Section: Discussionsupporting
confidence: 92%
“…Past efforts have evaluated environmental factors (e.g., weather, seasonal, land cover types) influencing spotlight counts (Progulske and Duerre , Rybarczyk , McCullough ), the accuracy of counts, and the precision of population indices (McCullough , Fafarman and DeYoung , Cypher , Whipple et al ). Although spotlight methods are capable of producing reliable indices of relative abundance for ungulates in some landscapes (Focardi et al , Garel et al , McShea et al , Anderson et al , Corlatti et al ), the effectiveness of spotlight counts to produce reasonable and precise estimates of density has remained inconsistent because of bias associated with study design, environment, or animal behavior (Focardi et al , McShea et al , Anderson et al ).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Further, roads are unlikely to be placed independently of topography (they avoid rugged terrain) or habitat (they favour dry ground), which may create larger-scale differences in density between areas near roads and areas far from roads. A recent study by McShea et al (2011) suggests bias in estimates of deer density can arise from non-random transect placement. Track-based surveys may need supplementary data, e.g.…”
Section: Ground-based Surveysmentioning
confidence: 99%
“…4.1). The assumption of representativeness needs to be tested by the investigator as demonstrated by Erxleben et al (2011);Hilário et al (2012); McShea et al (2011).…”
Section: Check-list For a Good Surveymentioning
confidence: 99%